If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
1/6-((11/12)*x)+1 = 6 // - 6
1/6-((11/12)*x)-6+1 = 0
(-11/12)*x+1/6-6+1 = 0
-11/12*x-29/6 = 0 // + 29/6
-11/12*x = 29/6 // : -11/12
x = 29/6/(-11/12)
x = -58/11
x = -58/11
| x^3+6x^2+3x=-18 | | 5x+3x+4x=189 | | 3-4/5w=-9 | | 2y+43=2 | | x^3-3x^2-x=-3 | | 2(-2)+4y=-16 | | (x+8)2=(x+7)2 | | -6-5=-8+x | | -7c+1=-27 | | 9x^4-42x^3+49x^2=0 | | 128x^2-24x+9=0 | | 5/t-5-2/t | | (x+1)=17 | | -6x=2x+16 | | 2-x+4-2x+3(x+2)=180 | | 7(3x-11y)+2x-5(x-6y)= | | -3x^2+2x+1=0 | | 144=(2/7)q | | x^2=12x-61 | | 2(w-2)+8=4-7w | | -x^2+28x-160=0 | | 5/2x | | 32x^3-98x=0 | | 1/3x-15+2/x-3 | | 1/4k-(k+1/4)=1/16(k+4) | | 9=1.5y | | 260=490-(5/7)q | | 9x^4-26x^2=0 | | 1/4x-8=5 | | 2.5y=-9 | | -x^2+28x-150=0 | | 1/5x-1/8x+1/40x=5 |